The dissipation of field emitting carbon nanotubes in an oxygen environment as revealed by in situ transmission electron microscopy. Issue 36 (5th September 2016) - Koh, Ai Leen; Gidcumb, Emily; Zhou, Otto; Sinclair, Robert
Abstract : In this work, we report the first direct experimental observations of carbon nanotubes (CNT) field emitting in an oxygen environment, using aberration-corrected environmental transmission electron microscopy in combination with an electrical biasing specimen holder. Abstract : In this work, we report the first direct experimental observations of carbon nanotubes (CNT) field emitting in an oxygen environment, using aberration-corrected environmental transmission electron microscopy in combination with an electrical biasing specimen holder under low-dose, field-free imaging conditions. Our studies show that while the CNTs remain stable during high vacuum field emission, they experience abrupt decreases in length, also termed "burn-back", when field-emitting in an oxygen environment at around 30 Pa pressure. Furthermore, we perform correlative field-free and aberration-corrected, high-resolution transmission electron microscopy imaging to understand how the structure of the CNTs – particularly the opening of the nanotube caps – is influenced by its gas environment during field emission. This work provides significant insight into the mechanism of carbon nanotube behavior under non-ideal field emission conditions.